Garçons manqués and femmes fortes: Two ambivalent figures of butch lesbianism in women's football in Cameroon - Ndjio, Basile (African Studies Review, 2022)
With the enactment of anti-homosexuality laws in the 1960s, Cameroon's government officially endorsed heterosexualist ideologies which legitimize the alienation and criminalization of minority and nonconforming sexual and gender identities. One group, the so-called garçons manqués, embodies the stigmatized masculine or "butch" lesbian identity. The political management of lesbianism in Cameroon is ambivalent, however, with respect to sport, and particularly regarding the national pastime, football. Whereas masculine lesbians are routinely branded as "butches" or "sexual predators" who threaten African hetero-patriarchy, "strong women"" (femmes fortes) are celebrated as pivotal to the national ambition. Cameroon's government strategically amalgamates both heteronationalism and homonationalism in the interest of national pride.
Keywords: afrique; anthropologie; approches et analyses; butch; cameroun; discipline; discours dominant; hétérosexisme; personnes lesbiennes; ressource en ligne; régions géographiques; sciences humaines; sexisme; sport; systèmes d'oppressions